Media Flipchart dalam Pembelajaran Kosa Kata Bahasa Arab: Tinjauan Masalah di MTS Sabilal Muhtadin - Fahrurrozi, Muhammad; Suparmanto, Suparmanto; Alparizi, Salman; Mardawiah, Mufidatul (STAINI Press, 2023)
Mufrodat for students is not easy, learning is boring and contains rote material making students’ interest in learning and student’ abiliti to study the material decrease. The use of flipchart media can help students improve their ability to interpret arabic. This study aims to determine the effectiveness of flipchart media to improve language mufrodat skills arab. The method used is qualitative research. The results of using this flipchart media show that this media is very effective for use in arabic vocabulary. This flipchart media can be used as an alternative arabic learning tool to help students become better arabic interpreters. Mufrodat for students is not easy, learning is boring and contains rote material making students’ interest in learning and student’ abiliti to study the material decrease. The use of flipchart media can help students improve their ability to interpret arabic. This study aims to determine the effectiveness of flipchart media to improve language mufrodat skills arab. The method used is qualitative research. The results of using this flipchart media show that this media is very effective for use in arabic vocabulary. This flipchart media can be used as an alternative arabic learning tool to help students become better arabic interpreters